2017
DOI: 10.1177/0148607117725043
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Obesity on Outcomes in Critically Ill Children

Abstract: In critically ill pediatric patients, being overweight or obese was associated with decreased need for intubation and inotropic support compared with normal-weight patients. However, being overweight or obese is neither protective nor a risk factor for mortality or duration of mechanical ventilation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…On the other hand, several studies have reported no association between BMI and mortality of critically ill patients. Supporting this claim, a recent study showed that although obesity decreases the need for intubation and inotropic support, evidence are not sufficient to support the increasing or decreasing mortality of patients (20). Another study on 312 patients with sepsis and acute respiratory failure showed that even though overweight and obese patients had an increased LoS in both hospital and ICU, there was no association between BMI and mortality rate (21).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, several studies have reported no association between BMI and mortality of critically ill patients. Supporting this claim, a recent study showed that although obesity decreases the need for intubation and inotropic support, evidence are not sufficient to support the increasing or decreasing mortality of patients (20). Another study on 312 patients with sepsis and acute respiratory failure showed that even though overweight and obese patients had an increased LoS in both hospital and ICU, there was no association between BMI and mortality rate (21).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the methods used to assess and classify nutrition status, the present study also differs from some previous studies. 13,14,16 For assessment of nutrition status, we only used WHO curves, the current international standard of optimal growth and development. Categories were established on the basis of BMI z-scores, chosen for their applicability to the entire study age range.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] An association has been proposed between overweight and pediatric PICU mortality 13 ; however, the literature so far shows heterogeneous studies producing conflicting results. [14][15][16] The objective of the present study was to determine whether excess weight is associated with clinical outcomes in critically ill children and adolescents admitted to the PICU.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, many studies have claimed that there is no correlation between the BMI and mortality outcomes of critically ill patients. Supporting this claim, a recent study showed although obesity has a direct impact on reducing the need of intubation and inotropic support, there is no signi cant evidence of an increase or decreasing in patients' mortality [26]. Another study on 312 patients with sepsis and acute respiratory failure showed that even though overweight and obese patients have an increased length of stay in both hospital and ICU, BMI is independent of mortality rate [27].…”
Section: Discussionmentioning
confidence: 99%
“…Still, obesity was signi cantly associated with longer length of stay and increased comorbid illness [28]. Recent studies are intended to evaluate the issue in larger study populations, among different subgroups, and according to the etiology context [26,29,30]. A recent dose-response meta-analysis regarding the effect of BMI on the mortality of ICU-admitted patients showed that for each unit of increase in BMI (kg/m2), a 0.6% decrease in mortality rate is expected [31].…”
Section: Discussionmentioning
confidence: 99%